A new motivation for heroin use: three diabetic cases - Cansel, N.; Savaş, H. A.; Özovacı, A.; Kalenderoğlu, A.; Savaş , E. (Journal of Dependence, 2008)
Opioids carry a high risk of addiction, but they are occasionally used as medical treatments due to their analgesic effects. Therefore, people begin using substances to relieve the pain caused by a chronic illness or, in some cases, to relieve psychiatric distress. However, to our knowledge, no cases have been reported in the literature of individuals who began using substances with the intention of treating diabetes—or regulating blood sugar—or developing addiction. This article will discuss the clinical experiences of three diabetic patients who began using heroin "in an attempt to treat their diabetes."
Keywords: heroin